Role Of Combination Of Multiple Herbal Drugs (Septilin) In The Prophylaxis Of Diabetic Foot Ulcer - A Double Blind Trial - Singh S.K (Wolters Kluwer Medknow Publications, 2001)
Infections, ischaemia and neuropathy are the major threats to diabetic foot apart from aerobic gram-negative organisms, anaerobic bacteria such as bacteriodes species play an important role in causing infection. Septilin, a polyherbal formulation with various constituents having antimicrobial, anti-inflammatory and immunomodulatory properties was evaluated in patients with diabetic foot ulcers. Septilin was administered at a dose of 2 tablets twice daily for 12 weeks. After 12 weeks of treatment, about 75% of the patients in group A had sterile would swab culture and 24% (approx) had some growth of E. coil and proteus. There was no growth of kelbsiella in this group. In group B. about 50% had recurrence of gram-negative infection and about 28% of patients showed gram-positive isolate in addition to gram-negative culture. Two patients in group B were dropped from the study due to high blood sugar levels.